Comparative analysis of external beam radiotherapy versus portal vein stent implantation combined with local and systemic therapy in hepatocellular carcinoma patients with portal vein tumor thrombus: a real-world retrospective study - Luo, Wenping; Wang, Guodong; Chen, Shaojun; Wang, Zhe; Li, Chuang; Yuan, Chunwang; Mao, Jingsong; Liu, Wenqi (Frontiers in Oncology, 2025)
ObjectiveTo compare the effectiveness and safety of External Beam Radiotherapy (EBRT) versus Portal Vein Stent Implantation (PVSI) when combined with local interventional therapy and TKI plus ICIs in patients with hepatocellular carcinoma (HCC) and portal vein tumor thrombus (PVTT), providing real-world evidence for clinical decision-making.MethodsThis retrospective cohort study included patients with HCC and PVTT who received either EBRT or PVSI in combination with transarterial interventional therapy, TKIs, and ICIs between January 2019 and January 2025. The primary effectiveness outcomes were overall survival (OS) and progression-free survival (PFS), which were analyzed using the Kaplan-Meier method and compared using the log-rank test. Secondary outcomes included objective response rate (ORR) and disease control rate (DCR) based on mRECIST criteria. Safety outcomes were assessed by documenting the incidence and severity of procedure-related complications and drug-induced liver injury according to CTCAE guidelines. Multivariate Cox regression and pre-specified subgroup analyses were performed to identify prognostic factors.ResultsThis study enrolled 67 patients (26 in the EBRT group and 41 in the PVSI group) with balanced baseline characteristics and a median follow-up of 21.0 months. The EBRT group showed superior efficacy, with significantly higher 6-month objective response (38.5% vs 14.6%, P = 0.028) and disease control rates (84.6% vs 58.5%, P = 0.025). Survival analysis demonstrated a significantly longer median overall survival in the EBRT group (35 months vs 19 months, P = 0.044), while the median progression-free survival was not reached, surpassing that of the PVSI group (11 months). Multivariate analysis identified EBRT treatment (HR=2.247, 95% CI: 1.090–5.404, P = 0.030) and AFP < 400 ng/mL (HR=0.329, 95% CI: 0.137–0.791, P = 0.013) as independent predictors of overall survival. Subgroup analysis further indicated that the survival benefit associated with EBRT was particularly pronounced among patients with VP2-type portal vein tumor thrombus and those receiving TKI combined with ICIs (median OS: 36 months vs 14 months, P = 0.017; 36 months vs 12 months, P = 0.005). The adverse event profiles varied between groups: grade 1-2 leukopenia was more common in the EBRT group (46.2% vs 7.3%, P<0.001), whereas grade 1-2 aspartate aminotransferase elevation was more common in the PVSI group (70.7% vs 38.5%, P = 0.009). Although grade 3-4 toxicities were generally infrequent, hyperbilirubinemia and hypoalbuminemia occurred relatively more often (approximately 20%) in the PVSI group.ConclusionThe combination of EBRT with local interventional procedures plus TKI and ICIs significantly improved survival in HCC patients with PVTT. The median overall survival (OS) was nearly doubled compared to those not receiving this combined approach, with particularly marked benefits observed in patients with VP2-type PVTT and those receiving TKI combined with ICIs. PVTT classification, liver function, and bone marrow reserve have a significant influence on prognosis. Additionally, AFP < 400 ng/ml (P < 0.05) and EBRT (P < 0.05) were identified as critical predictors of survival. However, this combined regimen was associated with increased treatment-related toxicities, necessitating careful hematologic monitoring during treatment.